Meaning-Centered Coping in the Era of COVID-19: Direct and Moderating Effects on Depression, Anxiety, and Stress - Eisenbeck, Nikolett; Carreno, David F.; Pérez-Escobar, José Antonio (Frontiers in Psychology, 2021)
The COVID-19 pandemic has subjected most of the world’s population to unprecedented situations, like national lockdowns, health hazards, social isolation and economic harm. Such a scenario calls for urgent measures not only to palliate it but also, to better cope with it. According to existential positive psychology, well-being does not simply represent a lack of stress and negative emotions but highlights their importance by incorporating an adaptive relationship with them. Thus, suffering can be mitigated (and transformed into growth) by, among other factors, adopting an attitude of positive reframing, maintaining hope, existential courage, life appreciation, engagement in meaningful activities, and prosociality. The conglomerate of these elements has been recently denominated as meaning-centered coping. In this study, we evaluated the protective role of this type of coping on mental health. A sample of 12,243 participants from 30 countries across all continents completed measures of Meaning-Centered Coping Scale (MCCS), depression, stress, anxiety and stressful COVID-19 related conditions they experienced. Results indicated that meaning-centered coping was strongly associated with diminished symptoms of stress, anxiety, and depression. Moreover, it moderated various relationships between vulnerability factors and markers of psychological distress, especially in the case of depression. These findings call for attention to meaning-centered coping approaches in the context of hardship, such as the current COVID-19 health crisis. In these difficult times, decision-makers and health organizations may integrate these approaches into their guidelines.